Cone and cone–rod dystrophy segregating in the same pedigree due to the same novel CRX gene mutation. Issue 8 (24th July 2008) - Kitiratschky, V B D; Nagy, D; Zabel, T; Zrenner, E; Wissinger, B; Kohl, S; Jägle, H
Abstract : Aim: To describe the detailed phenotypes of a multi-generation family affected by autosomal dominant cone–rod dystrophy (adCRD) and characterised by marked intrafamilial heterogeneity, due to a novel frameshift mutation in the CRX gene. Methods: Six affected and two unaffected family members underwent detailed ophthalmological examination as well as psychophysical and electrophysiological testing. Mutation screening of the CRX gene and segregation analysis were performed in 14 family members from three generations. Results: Clinical examination of six available mutation carriers showed marked phenotypic heterogeneity, presenting with a reduced cone electroretinogram (ERG) and normal rod ERG in one family branch and a negative ERG in the other as the most striking feature. Genetic screening identified a novel mutation in the CRX gene, c.636delC, that independently segregates with the disease in both branches of the family. Conclusion: The authors identified a novel disease causing mutation in the CRX gene associated with adCRD. Furthermore, we show here for the first time the coexistence of a reduced cone and a negative ERG component in different individuals of the same family, all affected by the same mutation.